Is ischemia-modified albumin a reliable tool for the assessment of acute pancreatitis? - Sahin, Abdurrahman; Turkoglu, Semra; Tunc, Nurettin; Duzenci, Deccane; Solmaz, Ozgen Arslan; Bahcecioglu, Ibrahim Halil; Yalniz, Mehmet (Dove Medical Press Ltd, 2018)
Purpose: Oxidative stress has been implicated in several disorders, including acute pancreatitis (AP). Ischemia-modified albumin (IMA), which reflects the ability to bind cobalt, has been found to be elevated in conditions of oxidative stress and tissue hypoxia. This study examined IMA and adjusted IMA levels in patients with AP, and examined the associations of IMA and adjusted IMA levels to the severity of AP. Patients and methods: A total of 42 consecutive patients with AP and 43 age-and sex-matched control subjects were enrolled. Serum samples were obtained from patients with AP on admission as well as 48-72 hours after hospitalization, and from the controls, at the time of enrollment. Adjusted IMA was calculated by multiplying the IMA value of each patient with the ratio of the patient's albumin value and the median albumin value of the study population. The severity of AP was assessed according to the modified Atlanta classification, and the patients were divided into 2 groups: mild AP and severe AP. Results: The serum IMA and adjusted IMA values of patients with AP on admission and those of the controls did not differ (p=0.86 and p=0.99, respectively). The second measurements of IMA and adjusted IMA in the AP group were higher than the first measurements of both the AP group and controls (for all, p<0.01). Among the IMA measurements, only adjusted IMA on admission had the ability to predict the severity of AP. Severe AP was correlated with albumin, and the area under the curve of adjusted IMA values on admission was 0.746 for differentiating patients with severe AP from mild AP with statistical significance (p=0.005). Conclusion: It was shown that IMA and adjusted IMA levels rise with the progression of AP. Lower levels of adjusted IMA predict the severity of AP. Further studies with serial measurements of IMA are warranted to explore the indicative role of IMA in the course of AP.
Keywords: ischemia modified albumin; adjusted ischemia modified albumin; acute pancreatitis; severity